Alcohol and tobacco: different tax policies and different health and revenue consequences in the 21st century in Poland - Neneman, Jarosław (Journal of Health Inequalities, 2022)
Over the last 20 years we can observe a divergence in health policies with respect to tobacco and alcohol that has led to significant health consequences. Poland experienced a significant increase in alcohol consumption accompanied by negative health and social consequences while, on the other hand, tobacco consumption went significantly down. Excise duty is one of the most important drivers for that. Alcohol excise policy was very passive, which resulted in a huge increase in the economic affordability of alcohol. Between 1999 and 2021 the number of bottles of vodka the disposable income could buy went up by 176%. At the same time, the tobacco tax policy was active so that the economic affordability of cigarettes did not change at all. This article presents the data on taxes, affordability and tax revenues and tries to explain this divergence. Three perspectives (health, financial and political) are sketched to show the predominant incentives for the players.